Embryonic cell migratory capacity is impaired upon exposure to glucose in vivo and in vitro - Herion, Nils Janis; Kruger, Claudia; Staszkiewicz, Jaroslaw; Kappen, Claudia; Salbaum, J. Michael (Birth defects research, 2019)
Background Impairments in cell migration during vertebrate gastrulation lead to structural birth defects, such as heart defects and neural tube defects. These defects are more frequent in progeny from diabetic pregnancies, and we have recently provided evidence that maternal diabetes leads to impaired migration of embryonic mesodermal cells in a mouse model of diabetic pregnancy. Methods We here report the isolation of primary cell lines from normal and diabetes-exposed embryos of the nonobese diabetic mouse strain, and characterization of their energy metabolism and expression of nutrient transporter genes by quantitative real-time PCR. Results Expression levels of several genes in the glucose transporter and fatty acid transporter gene families were altered in diabetes-exposed cells. Notably, primary cells from embryos with prior in vivo exposure to maternal diabetes exhibited reduced capacity for cell migration in vitro. Conclusions Primary cells isolated from diabetes-exposed embryos retained a “memory” of their in vivo exposure, manifesting in cell migration impairment. Thus, we have successfully established an in vitro experimental model for the mesoderm migration defects observed in diabetes-exposed mouse embryos.
First published: 19 November 2018
Gesehen am 05.12.2019